Algunas anotaciones sobre la formación gualanday (1985)
On comparing the various tertiary, sedimentary formations of Colombia, their petrographic caracteristics, their sedimentary structures (therefore their depositional enviromment), their geophysical caracteristics and their morphology, with those of the Gualanday Formation, one notices no correlation. There are, on the other hand, many reasons to consider that the Gualanday is precretaceous and probably related to the Girón Formation.